Automatización del Perfil de Calentamiento de una Extrusora de Polímeros en UAN Cali (2011)
This document is a compilation of the results obtained during the design and implementation of a temperature control system of the extruding machine located at the laboratory of polymers of the Universidad Antonio Nariño – Cali.